Evaluation of homogeneity of active ingredient inside infantile suppository body Example: sodium diclofenac suppositories (Journal of Hama University, 2019)
Suppositories are widely used pharmaceutical dosage form especially for children and infants taking in account their privileges in comparing with oral forms. Suppositories should characterized by good specifications so its under go different quality control tests as visual inspection, disintegration and melting tests, uniformity of weight and assay. The latter does not reflect the homogeneity of active ingredient alongside suppositories body so it should be assessed by sectioning a suppository cross-section into three equal parts, and ensuring that each section presents the same quantity of drug. This test is so important in order to avoid the local irritation in rectum and as an indicator for good manufacturing. In this work , from two pharmaceutical companies A and B, eight different batches of sodium diclofenac suppositories for child of two strength 12.5 mg and 25 mg have been evaluated. Visual examination and physical tests have been carried out then we concentrate on assay and homogeneity of distribution of active ingredient inside suppository body.  All batches are  in conform with physical and visual tests. We find that batches of 12.5 mg contain the lowest permitted limit while all batches of the strength 25 mg are in accordance with pharmacopoeial limits. No significant differences have been observed between the two companies concerning the same strength. However, the test of homogeneity inside suppository shows that batches from company B of two strengths present a good distribution pattern since the percentage of drug in each third is about 30-35% disregard the strength while the percentage of drug at the top of suppository is about 50% in batches from company A. This work confirms the importance of carrying out this latest test simultaneously with the assay and recommends not to divide suppository as a manner to diminish the dose.